Retrospective analysis of 191 dogs with mitral valve disease based on tomazzo et AL.’s mitral insufficiency echocardiographic score - Santos, André Avelino Silva (2022)
Dissertação de Mestrado Integrado em Medicina Veterinária, área científica - Clínica